To conduct the proximate analysis of given reductant (coal/coke/charcoal). - Rao, Lakkoju Sankara (Main Library, IIT (BHU), Varanasi, 2022)
To conduct the proximate analysis of given reductant (coal/coke/charcoal). (a)This video shows gives the introduction of proximate anlaysis. (b) Shows the procedure of finding the Proximate analysis (Moisture, Volatile matter, Ash and Fixed carbon). PART 1 Introduction PART 2 Proximate Analysis Procedure PART 3 Drop Strength& Crushing Strength PART 4Experiment &Results